Maturity-onset diabetes of the young (MODY): current perspectives on diagnosis and treatment - Urakami T (Diabetes, Metabolic Syndrome and Obesity, 2019)
Tatsuhiko UrakamiDepartment of Pediatrics, Nihon University School of Medicine, Tokyo, JapanAbstract: Maturity-onset diabetes of the young (MODY) is characterized by autosomal dominant inheritance, onset before 25 years of age, absence of β-cell autoimmunity, and sustained pancreatic β-cell function. To date, mutations have been identified in at least 14 different genes, including six genes encoding proteins that, respectively, correspond to MODY subtypes 1–6: hepatocyte nuclear factor (HNF) 4α (HNF4α), glucokinase (GCK), HNF1α (HNF1α), pancreatic and duodenal homeobox 1 (PDX1), HNF1β (HNF1β), and neurogenic differentiation 1 (NEUROD1). Diagnostic tools based on currently available genetic tests can facilitate the correct diagnosis and appropriate treatment of patients with MODY. Candidates for genetic testing include nonobese subjects with hyperglycemia, no evidence of β-cell autoimmunity, sustained β-cell function, and a strong family history of similar-type diabetes among first-degree relatives. Moreover, identification of the MODY subtype is important, given the subtype-related differences in the age of onset, clinical course and progression, type of hyperglycemia, and response to treatment. This review discusses the current perspectives on the diagnosis and treatment of MODY, particularly with regard to the six major subtypes (MODY 1–6).Keywords: MODY, molecular diagnosis, genetic testing, pharmacological treatment